Modalitas Dalam Keterpilihan Kandidat Pada Pemilu Legislatif 2014 - Sirait, Maydi Zefanya; Noak, Piers Andreas; Ali Azhar, Muhammad (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2020)
ABSTRACT Competition in the political arena does not only include party competition space using social capital. Capital is a trust that a candidate pair has with the peoplewho voted for it. Social capital according to Putnam said social relations involving networks, norms, and social trust. This study uses qualitative research methods, while the source of the data used is primary and secondary data, namely direct observation, interviews, and literature under this study. Data analyzed with qualitative analysis. The basis of the theory uses the theory of social capital put forward by Putnam, namely Social Capital. Research results, conclusions, modalities, determination of successful actors in politics. Individual capital owned by the actor is a f oundation that is formed from a thin belief. Thin belief as a step for actors to build community participation. Thick trust is obtained from the family's social capital obtained as the village head. Keywords: Social Capital, High Level Trust, Low Level Trust, Legislative Elections.